Analisis Faktor Penentu Pembiayaan Bank Syariah Di Indonesia - Desi Anggarwati; Idah Zuhroh (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to analyze the determinants of financing in Islamic banking in Indonesia. The independent variables in the study are Third Party Funds (DPK), Return on Assets (ROA), Financing to Deposit Ratio (FDR), Minimum Capital Adequacy Requirement (KPMM), Non-Performing Financing (NPF_Gross), Against Islamic Commercial Banks in Indonesia. . The population used in this study were all Indonesian Islamic banking for the 2010-2020 period, namely 14 banks. The sample of this research is using 8 Islamic banking. With the sampling method, namely purposive sampling. The results of this study are that the third-party funds (DPK) have a positive and significant effect on Islamic bank financing. Return on Asset (ROA) has a negative and significant effect on Islamic bank financing. Financing to Deposit Ratio (FDR) has a positive and significant effect on Islamic bank financing. Minimum Capital Adequacy Requirement (KPMM) has a positive and insignificant effect on Islamic bank financing. Non-performing financing (NPF_Gross) has a negative and significant effect on Islamic bank financing.